Hubungan Kepemimpinan Spiritual dan Budaya Organisasi dengan Kepuasan Kerja Karyawan PT Sinar Sakti Kimia - Sheena Junita; Eddy M Sutanto (TRIKONOMIKA, 2015)
This research was conducted to find out the job satisfaction of employees in relation to spiritual leadership and organizational culture. The aim is to contribute to the academic and business research, so knowing how to maximize employee job satisfaction. The analysis techniques used in this research is with the method of chi square and pearson correlation, both methods are used to determine the relati on ship between research variables occur. The results showed that job satisfaction has a positive relationship is indi cated by the value of the coefficient contingency 0,520 for variables of spiritual lead ership and job satisfaction and the value of the coefficient contingency 0,550 for variables of organizational culture and job satisfaction. Variable spiritual lead er ship and organizational culture each have a strong relationship with job satis fac tion is evident from the r value of 0.524.